THE POTENTIAL EFFECT OF KUKKUTANDA SWEDA IN THE MANAGEMENT OF MANYASTAMBHA W.S.R. CERVICAL SPONDYLOSIS - Rajput Prakash Singh; Mishra Nidhi; Shukla Umesh (International Journal of Applied Ayurved Research, 2017)
Backgrounds - Manyastambha is the clinical condition in which the back of the neck becomes stiff and the movements of the neck are impaired. Manyastambha has been included in Eighty Nanatmaja vata-vyadhi. It can be co-related with Cervical Spondylosis in modern medicine. Cervical Spondylodis is a degenerative condition of the cervical spine. Pain and stiffness are the primary symptoms. If severe, it may cause pressure on nerve roots with subsequent sensory or motor disturbances. In today’s busy world people work hours on computers, night jobs, take day sleep, take long drives, sleep over abnormally and give least importance to proper physical, mental exercise & food habits. 66% of adults experience neck pain in their lifetime and 5% are highly disable by it. Aim – To explore the role of panchkarma specially Kukkutanda pinda Sweda in management of Manyastambha. Panchakarma is the specific Ayurvedic treatment process for the purpose of detoxification of the body through 5 specific natural physical processes. Material & method - In the present study, we collected and compiled about Manyastambha & Kukkutanda pinda Sweda from classical text & related data of different websites have critically reviewed. For explain the mechanism of Kukkutanda pinda Sweda in management of Manyastambha, the collect material arrange in such manner.Discussion & conclusion - Modern modalities have a lot of limitations along with side effects and expenditure. Ayurvedic management can effectively manage this condition. Swedan karma releases sthambha (stiffness) and pacify vitiated vata so Shula (pain) is decreased. Kukkutanda (Indian hen egg) Pinda Sweda is having properties of Kapha-vatahar and Brihmana properties are supposed to be beneficial in Manyastambha.